A busca pela prática docente como alfabetizadora: minhas histórias no município de Igarapé-Miri/PA - AIRES, Olinda Quaresma (2019)
The present work has as its theme: "The search for teaching practice as a literacy teacher: my stories in the municipality of Igarapé-Miri / PA". It aimed to relate the aspects of my childhood life, to teaching and later in higher education. Thus, the chosen theme is justified by the fact that it deals with a real life experience, in my case, portraying my reality and being able to relate teaching experience, from action-reflection-action, through theoretical and practical knowledge. acquired in the academy, making it possible to reflect the processes by which our pedagogical practice is constituted in educational and social practice. For that, my work was carried out, through my own reports of experiences, steps taken in the course of my social and professional life, as well as through bibliographic material, theoretical basis of authors who adhere to the theme to base my work. In this way, this work is based on three chapters: first, my life story: from birth to the family context, with the following subtopics: my family experience: childhood memories; first school and literacy; elementary School. In the second chapter I approached the professional construction, with the following sub-themes: my training in teaching; performance in teaching. In the second chapter I approached the professional construction, with the following sub-themes: my training in teaching; performance in teaching.